2022
DOI: 10.1111/josh.13229
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to High School Meal Program Participation: A Qualitative Study of Students and Their Caregivers

Abstract: BACKGROUND:The school food environment is a critically important area to target the health of millions of students, especially those experiencing food insecurity. However, both students and caregivers have noted significant barriers to participation in the school meal program, including taste, lunchroom experience, and limited availability of fresh, healthy foods. There is a lack of qualitative research which considers both caregiver and adolescent perspectives, particularly among youth of color.METHODS: Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We identified greater dietary impacts of the 2020 DGA-aligned nutrition standards among elementary and middle school than high-school students, largely because of the lower participation rates in school meals among high-school students [ 48 ]. Identified barriers to school meal participation may include the taste and quality of school meals and the stigma of receiving free or reduced price school meals [ 49 ], and high-school students may be more sensitive to these barriers compared to younger age groups [ 48 ]. Interestingly, the SNMC study found that healthier school meals (measured by the Healthy Eating Index) were associated with higher overall participation rates than less healthy school meals [ 50 , 51 ], suggesting that improvements in nutritional quality may increase participation.…”
Section: Discussionmentioning
confidence: 99%
“…We identified greater dietary impacts of the 2020 DGA-aligned nutrition standards among elementary and middle school than high-school students, largely because of the lower participation rates in school meals among high-school students [ 48 ]. Identified barriers to school meal participation may include the taste and quality of school meals and the stigma of receiving free or reduced price school meals [ 49 ], and high-school students may be more sensitive to these barriers compared to younger age groups [ 48 ]. Interestingly, the SNMC study found that healthier school meals (measured by the Healthy Eating Index) were associated with higher overall participation rates than less healthy school meals [ 50 , 51 ], suggesting that improvements in nutritional quality may increase participation.…”
Section: Discussionmentioning
confidence: 99%
“…Data included in this study came from two separate studies [ 14 , 15 ]. We included data from both studies to increase our sample size and to be able to include participants from across the adolescent—early adult developmental period.…”
Section: Methodsmentioning
confidence: 99%
“…Study materials were available in both English and Spanish translation to ensure inclusivity of students and caregivers of ethnically diverse backgrounds. Focus groups were held for about 60 minutes and focused on 3 main areas of interest: (1) school communication preferences and opinions about digital health tools, (2) daily school meal participation and decision‐making about school meals, 33 and (3) overall nutrition knowledge. The current paper explores the results from the first area of interests related to communication preferences and digital health tools.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents also suggested that the app could be used to gather feedback on the food and menu options, which could be important for increasing participation in NSLP as previous research has shown that perceptions of school lunch quality and taste can be a barrier to participation. 33 Some respondents identified potential barriers related to accessibility due to lack of internet connectivity in schools and also raised concerns around the schools' ability to afford an incentivized mobile application. Future research pertaining to specific barriers and facilitators around the development digital interventions is necessary to gain full understanding.…”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
See 1 more Smart Citation